Transformation of Pesantren Education as a Starting Point for Religious Moderation in Indonesia - Abdul Hadi; Ishak Syairozi; Marliza Oktapiani (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2024)
Pesantren education, as a cornerstone of Indonesia's educational system, plays a significant historical and cultural role in shaping religious understanding and national character. However, its role as an agent of change in promoting civility and humanity remains underexplored. This qualitative case study investigates how the transformation of pesantren education, particularly through curriculum integration, fosters religious moderation. Data were collected through in-depth interviews, observations, and documentation at pesantren in West Java, Indonesia, and analyzed thematically. Findings reveal that the integration of national and local curricula significantly enhances students' moderate attitudes across four dimensions: national commitment, tolerance, anti-violence, and respect for local culture. This study contributes to understanding how pesantren can adapt to modern challenges by aligning traditional Islamic education with inclusive and pluralistic values, thus strengthening their role in creating a harmonious society.